NL scoring and Bloom competency test: an experimental result - Lajis, Adidah; Abdul Aziz, Normaziah (2012)
Assessing learner' answers is an important task and also require a lot of time. In many cases, exam papers comprise of questions that require learners to write at least one or two sentences to express their understanding. However, there are not many computer-based assessment tools able to cater the needs due to limitations in computerized marking technology. This research attempts to address this limitation by introducing a technique to evaluate short free text answer. It is based on a hybrid approach that combines natural language processing and artificial intelligence. A textual answer is converted into a node link representation to extract the hidden knowledge structure. We then apply information theory approach to compute learners understanding which gives a result in bit. The assessment also has been done for testing Bloom competency. Results have shown that Bloom competency can be assessed via assisted assessment.